Taxonomically Restricted Wheat Genes Interact With Small Secreted Fungal Proteins and Enhance Resistance to Septoria Tritici Blotch Disease - Brennan, Ciarán J.; Zhou, Binbin; Benbow, Harriet R.; Ajaz, Sobia; Karki, Sujit J.; Hehir, James Gerard; O’Driscoll, Aoife; Feechan, Angela; Mullins, Ewen; Doohan, Fiona M. (Frontiers in Plant Science, 2020)
Understanding the nuances of host/pathogen interactions are paramount if we wish to effectively control cereal diseases. In the case of the wheat/Zymoseptoria tritici interaction that leads to Septoria tritici blotch (STB) disease, a 10,000-year-old conflict has led to considerable armaments being developed on both sides which are not reflected in conventional model systems. Taxonomically restricted genes (TRGs) have evolved in wheat to better allow it to cope with stress caused by fungal pathogens, and Z. tritici has evolved specialised effectors which allow it to manipulate its host. A microarray focused on the latent phase response of a resistant wheat cultivar (cv. Stigg) and susceptible wheat cultivar (cv. Gallant) to Z. tritici infection was mined for TRGs within the Poaceae. From this analysis, we identified two TRGs that were significantly upregulated in response to Z. tritici infection, Septoria-responsive TRG6 and 7 (TaSRTRG6 and TaSRTRG7). Virus induced silencing of these genes resulted in an increased susceptibility to STB disease in cvs. Gallant and Stigg, and significantly so in the latter (2.5-fold increase in STB disease). In silico and localisation studies categorised TaSRTRG6 as a secreted protein and TaSRTRG7 as an intercellular protein. Yeast two hybrid analysis and biofluorescent complementation studies demonstrated that both TaSRTRG6 and TaSRTRG7 can interact with small proteins secreted by Z. tritici (potential effector candidates). Thus, we conclude that TRGs are an important part of the wheat-Z.tritici co-evolution story and potential candidates for modulating STB resistance.